Anti-corruption mechanisms in the public procurement system: prevention of abuse at the tender stage - Pavliuk, Tetiana; Polusmiak, Yuliia; Polovynkina, Ruslana; Davidenko, Oksana (Management and Entrepreneurship: Trends of Development, 2025)
This article explores the pressing issues of preventing corruption in Ukraine’s public procurement system, with a specific focus on the tendering stage. It highlights the academic and practical imperative to enhance anti-corruption mechanisms to optimize the use of public funds. The study aims to analyze contemporary anti-corruption strategies within public procurement and to develop actionable recommendations for mitigating malpractices during tendering processes. Employing a comprehensive methodological approach, the research utilizes a combination of general scientific and specialized methods. These include systematic analysis to define the essence of corruption risks and anti-corruption mechanisms, comparative analysis to assess the effectiveness of various anti-corruption measures, expert assessments to identify typical corruption schemes, and inductive and deductive reasoning to formulate conclusions and recommendations. The study draws upon legislative acts, statistical data, research findings, and judicial precedents. The results of the analysis provide an overview of the current anti-corruption mechanisms in Ukraine’s public procurement system, identify common corruption risks at the tendering stage, and propose practical recommendations to prevent abuses. The findings emphasize the need for continuous improvement of procurement practices and the importance of transparency and accountability in public spending. JEL Classification: H5, M 21, K42, D7